Effect of adhesive types on enamel discolouration around orthodontic brackets - Jahanbin Arezoo; Ameri Hamideh; Khaleghimoghaddam Rokhsareh (Sciendo, 2023)
Unsightly colour changes may occur in the enamel around bonded orthodontic brackets.